Conception of Sustainable Development in Local Philosophies of Scandinavian Countries - Borre Bragdo, Magnus; Tuszyńska, Ligia; Żeber-Dzikowska, Ilona (Studia Ecologiae et Bioethicae, 2023)
This article was inspired by the cooperation between two university teams implementing a Polish-Norwegian project Green Schoolbag for the Earth Climate. The project was aimed at preparing early school pedagogy teachers and students for the implementation of education for sustainable development (SD). A study trip to Norway and sharing experience gave rise to studying Norwegian curricula and educational literature. The study findings revealed that local educational philosophies and SD in the four Scandinavian countries differ in social, cultural and educational terms. The article presents the historical background to introducing SD into social and cultural habits in each of the countries and, consequently, lifestyles typical of the inhabitants of these countries. Four types of lifestyles are compared: Finish sisu, Norwegian friluftsliv, Danish hygge and Swedish lagom. The analysis proved that Scandinavian countries have similar climate and values as regards their attitudes to nature. However, differences in local philosophies are visible and their inhabitants present specific lifestyles, different behaviours and social and cultural principles behind their attitudes to the SD concept. The conclusion of the article puts an open question about Polish people’s local philosophy, lifestyle and SD education.